Multiferroic properties of lead-free Ni0.5Zn0.5Fe1.9O4−δ−Na0.5Bi0.5TiO3 composites synthesized by spark plasma sintering. Issue 5 (June 2015) - Mudinepalli, Venkata Ramana; Song, S.-H.; Ravi, M.; Li, J.-Q.; Murty, B.S.
Abstract: Multiferroic composites of x Ni0.5 Zn0.5 Fe1.9 O4− δ −(1− x ) Na0.5 Bi0.5 TiO3 ( x NZF−(1− x ) NBT, where x =0.05, 0.15 and 0.25 mol fraction) were synthesized by spark plasma sintering (SPS) in conjunction with high-energy ball milling. The presence of NZF and NBT phases in the composites was confirmed by X-ray diffraction. The dielectric constant was studied as a function of frequency (0.5 kHz to 1 MHz) and temperature (30–500 °C). It was found that the 0.25 NZF–0.75 NBT composite possessed the most promising dielectric properties with its dielectric constant being 5–10 times higher than those for the other two composites in the full range of frequency. The magnetic and ferroelectric properties were examined at room temperature and all composite samples exhibited both pronounced ferromagnetic and ferroelectric characteristics. A maximum ME voltage coefficient of 870 μV/cm Oe was obtained at the magnetic field of 1.25 kOe for the 0.25 NZF–0.75 NBT composite, which was well comparable with the ME output for the lead-containing NZF–PZT composites.